2003
DOI: 10.7326/0003-4819-139-11-200311180-00013
|View full text |Cite
|
Sign up to set email alerts
|

Test Performance of Positron Emission Tomography and Computed Tomography for Mediastinal Staging in Patients with Non–Small-Cell Lung Cancer

Abstract: Positron emission tomography with 18-fluorodeoxyglucose is more accurate than CT for mediastinal staging. Positron emission tomography with 18-fluorodeoxyglucose is more sensitive but less specific when CT shows enlarged mediastinal lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
334
4
41

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 645 publications
(387 citation statements)
references
References 82 publications
8
334
4
41
Order By: Relevance
“…A large meta-analysis reported that the average sensitivity and specificity for LN staging were approximately 85 % and 90 %, respectively [15]. The present study showed comparable sensitivity (84.7 %).…”
Section: Discussionsupporting
confidence: 58%
“…A large meta-analysis reported that the average sensitivity and specificity for LN staging were approximately 85 % and 90 %, respectively [15]. The present study showed comparable sensitivity (84.7 %).…”
Section: Discussionsupporting
confidence: 58%
“…I ntegrated positron emission tomography/x-ray computed tomography (PET/CT) imaging is widely used for the diagnosis and staging of patients with various types of thoracic lesions [1][2][3]. However, PET data acquisition occurs over many respiratory cycles and as such, accurate evaluation of thoracic lesions on PET/CT may prove challenging due to respiratory motion during imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Mediastinoscopic (McNeill and Chamberlain, 1966) or VATS approaches are usually reserved for cases when other measures cannot yield the diagnosis. There have been still very limited reports about the application of VATS in the diagnosis of sarcoidosis in (Massone et al, 2003;Ohmichi, 2002;Nakayama et al, 2000;Gould et al, 2003). In TB high prevalence area, patients with hilar or mediastinal lymphadenopathy should be differentiated pathologically between sarcoidosis and tubeculosis (Nakayama et al, 2000).…”
Section: Discussionmentioning
confidence: 99%